2013
DOI: 10.1175/jcli-d-12-00727.1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Regional Climate Model Grid Spacing for the Simulation of Heavy Precipitation in the Colorado Headwaters

Abstract: Summer and winter daily heavy precipitation events (events above the 97.5th percentile) are analyzed in regional climate simulations with 36-, 12-, and 4-km horizontal grid spacing over the headwaters of the Colorado River. Multiscale evaluations are useful to understand differences across horizontal scales and to evaluate the effects of upscaling finescale processes to coarser-scale features associated with precipitating systems.Only the 4-km model is able to correctly simulate precipitation totals of heavy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 21 publications
(24 reference statements)
11
90
0
Order By: Relevance
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
“…This will, naturally, highlight the improved representation of the natural spatial variability of rainfall arising from local dynamical gradients, orography, etc., in higher-resolution models. Indeed, Prein et al (2013) commented that "The major advantages of high-resolution simulations are found for small scales" and that, at scales above ∼ 100 km, their higher-resolution runs show only "small advantages" over their lower-resolution runs. However, Kopparla et al (2013) point out that such comparisons differ between regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other authors reported no improvements in the simulations of daily mean precipitation by the convection-permitting models compared with large-scale climate models (Chan et al, 2013;Fosser et al, 2015). Some other researchers found improvements, especially over mountainous areas (Prein et al, 2013b;Ban et al, 2014), implying region and model dependency for simulation of daily mean precipitation. In our study, the higher skill of the ALARO CNRM-CM3 model in sim- ulation of summer precipitation extremes appears to be because of a better representation of the small-scale characteristics and spatial variability relevant for convection (Fig.…”
Section: Validation Of Precipitation Simulationsmentioning
confidence: 99%
“…The nudging ensures that synoptic-scale features are similar to the observations while sub-synopticscale processes such as the upscale growth and organization of MCSs can freely evolve. The final model setup is based on a series of sensitivity test that incorporated model physics (Liu et al 2011(Liu et al , 2016 and model grid spacing (Ikeda et al 2010;Prein et al 2013b). Additional information about the simulation can be found in Liu et al (2016).…”
Section: Model Setup and Observational Datamentioning
confidence: 99%